Integrity risk evaluation of impact of ionospheric anomalies on GAST D GBAS. Issue 2 (3rd January 2020) - Yoon, Moonseok; Lee, Jiyun; Pullen, Sam
Abstract: This study develops a three‐step Monte Carlo method to evaluate the worst possible integrity risk of ionospheric spatial gradients for GAST D GBAS. Impact simulation parameters are classified into two groups, "worst‐case" and "average, " based on the underlying integrity requirements. Unlike "average" parameters, "worst‐case" parameters are those for which a clear basis for averaging could not be established because the probabilistic distribution of these parameters cannot be developed with sufficient confidence due to the lack of observation data. In calculating integrity risk, these "worst‐case" parameters use the worst‐case value that maximizes the integrity risk. Each step of the randomized search narrows down the parameter ranges in sequence and identifies the two worst‐case parameter sets (based on the largest position error and the largest missed‐detection probability) for each worst‐case region identified in the initial step. The resulting integrity risk values are well below 10 −9, showing that the GAST D SARPs integrity requirement is met.